Tackling agrifood waste in Ghana: resource recovery technologies and lessons from urban open-air markets - Somorin, Tosin; Afolabi, O.; Nartey, Eric Gbenatey; Amponsah, Andoh; Ayertey, Desmond; Sedenkor, D.; Asiamah, T.; Gebrezgabher, Solomie A. (International Water Management Institute, 2025)
Open-air markets are essential for food access and livelihoods in Sub-Saharan Africa, but they generate large amounts of mixed, moisture-rich organic waste that current management systems struggle to handle. Poor segregation, inadequate infrastructure, and limited processing capacity lead to environmental damage, health risks, and missed opportunities for resource recovery. This report reviews current waste-to-value technologies and their suitability for diverse market waste, based on consultations, technical evaluations, and literature review. Standalone methods, such as composting, anaerobic digestion, and black soldier fly systems, show promise but face challenges due to the heterogeneity of waste. Adoption is further limited by high capital and operating costs, unreliable utilities, restricted financing options, and weak maintenance systems. Informal waste practices, low awareness of the benefits of the circular bioeconomy, and limited incentives also impede progress. Unlocking the circular bioeconomy potential in these markets requires integrated, scalable solutions, enhanced infrastructure, technical support, and thorough financial and feasibility evaluations to ensure lasting sustainability. Successful implementation requires better source segregation, upgraded facilities, and supportive governance structures.